Stevens-Johnson syndrome and toxic epidermal necrolysis: A fresh look at an old foe - Sowmya Kaimal; Carol Lobo; Girish Narayan; Mary Augustine (Wolters Kluwer Medknow Publications, 2023)
Background: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are some of the less common cutaneous adverse drug reactions with significant mortality. Objectives: This study was undertaken with the objective of studying the demographics and clinical profile of SJS/TEN and identifying parameters associated with mortality. Materials and Methods: All patients with SJS/TEN over 10 years (2010-2020) were included in the study. Data obtained from in-patient and out-patient records were analysed. Results: A total of 82 patients with SJS/TEN were admitted to our centre over a period of 10 years. Patients with SJS were significantly younger than those with TEN, with a male: female ratio >1 in SJS and <1 in TEN. The most commonly implicated drugs were antiepileptics (n = 29, 35.4%), antibiotics (n = 20, 24.4%). and Non-steroidal antiinflammatory drugs (NSAIDs) (n = 7, 8.5%). The mortality rate in the TEN group was 16% (n = 8). Certain factors such as cutaneous lesions preceding mucosal lesions at onset, high mean Body surface area (BSA) of denudation and a transfer to intensive care unit (ICU) more than 7 days after admission were significantly associated with higher mortality. There was no difference between survivors and deaths in terms of delay in hospitalisation, total disease duration, implicated drug, delay in initiation of therapy, the onset of re-epithelialisation, Severity-of-illness score for TEN (SCORTEN) and total duration of hospital stay. Conclusion: Factors significantly associated with increased mortality in TEN were cutaneous onset of lesions, mean BSA of involvement and transfer to the intensive care unit (ICU) beyond day 7 of admission.